Protesta altermundista y violencia política en Guadalajara - Guerra Blanco, Edgar Everardo (El Colegio de México, 2014)
In order to explore the relationship between political violence and social protest, this paper deals with the subject matter from the theoretical perspective of the political process and the mobilization of resources in a case study: the alterglobalist mobilizations in the city of Guadalajara, Jalisco in the context of the III Summit of the Heads of State and Government of Latin America, Europe and the Caribbean (alcuE) in May of 2004. Through a qualitative research design, it analyzes the complex interrelationship between the organizations and globalist collectives, their cultural frames and history of contention, and the dynamics of the local political process, in order to understand how these factors influenced the dynamics of the protest events and conditioned the episodes of political violence in its two main forms: physical and symbolic.